Experimental behavior of SFRC columns under uniaxial and biaxial cyclic loads. (February 2016) - Germano, Federica; Tiberti, Giuseppe; Plizzari, Giovanni
Abstract: The use of Steel Fiber Reinforced Concrete (SFRC) was experimentally evaluated with the aim of verifying its effectiveness in reducing the damage and improving the ductility as well as the energy dissipation of seismic resistant columns with special emphasis to the base regions where plastic hinges develop. Sixteen full-scale cantilever columns were tested under reversing cyclic lateral loading and constant axial load. Both unidirectional (uniaxial) and bidirectional (biaxial) lateral displacements were imposed in order to better simulate the actual response of a column during an earthquake. A volume fraction of 1.0% of steel fibers was adopted together with different percentages of transverse reinforcement; the latter was adopted with two steel grades having different ductility performance in order to evaluate their influences on the column behavior. The results of the experimental campaign confirmed that SFRC may reliably reduce the columns damage by preventing the concrete cover to spall out at earlier stages and increase their initial stiffness and energy dissipation, especially for uniaxial loads that resulted less severe than the biaxial ones.